The Taiwanese species of the genus Paraphloeostiba Steel, 1960 (Coleoptera: Staphylinidae: Omaliinae: Omaliini) - Shavrin, Alexey V.; Smetana, Aleš (Zootaxa, 2016)
Paraphloeostiba formosana sp. n. from Taiwan is described. Paraphloeostiba sonani (Bernhauer, 1943) is redescribed, the lectotype of Phloeonomus sonani Bernhauer, 1943 is designated. Both species are illustrated. A key to the species of Paraphloeostiba Steel, 1960 of Taiwan is given.